Correction: Psychotic Experiences and Overhasty Inferences Are Related to Maladaptive Learning. - Heiner Stuke; Hannes Stuke; Veith Andreas Weilnhammer; Katharina Schmack (PLoS Computational Biology, 2017)
[This corrects the article DOI: 10.1371/journal.pcbi.1005328.].